Quantification and biodegradability assessment of meso-2, 3-dimercaptosuccinic acid adsorbed on iron oxide nanoparticles. Issue 9 (16th August 2019) - Bemowsky, S.; Rother, A.; Willmann, W.; Köser, J.; Markiewicz, M.; Dringen, R.; Stolte, S.
Abstract : An analytical method was developed to quantify the amount of free and nanoparticle-bound dimercaptosuccinic acid to address the question whether or not the coating material is biodegradable. Abstract : Many interesting applications of magnetic iron oxide nanoparticles (IONPs) have recently been developed based on their magnetic properties and promising catalytic activity. Depending on their intended use, such nanoparticles (NPs) are frequently functionalized with proteins, polymers, or other organic molecules such as meso-2, 3-dimercaptosuccinic acid (DMSA) to improve their colloidal stability or biocompatibility. Although the coating strongly affects the colloidal properties and environmental behaviour of NPs, quantitative analysis of the coating is often neglected. To address this issue, we established an ion chromatographic method for the quantitative analysis of surface-bound sulfur-containing molecules such as DMSA. The method determines the amount of sulfate generated by complete oxidation of sulfur present in the molecule. Quantification of the DMSA content of DMSA-coated IONPs showed that reproducibly approximately 38% of the DMSA used in the synthesis was adsorbed on the IONPs. Tests for the biodegradability of free and NP-bound DMSA using a microbial community from a wastewater treatment plant showed that both free and NP-bound DMSA was degraded to negligible extent, suggesting long-term environmental stability of DMSA-coated IONPs.